Teaching Basic Special Relativity in High School: The Role of Classical Kinematics - Arlego, Marcelo José Fabián (2017)
In this work, we present a possible didactic sequence for the study of basic aspects of special relativity in high school. The sequence re-signifies the role of classical kinematics and Galileo´s relativity principle. It has been implemented in four courses of two secondary schools in Argentina in 2014-2015 and in Colombia in 2016, with students aged 15-16, during 20 school hours, being the teacher a member of our research team.